2023
DOI: 10.7554/elife.85542
|View full text |Cite
|
Sign up to set email alerts
|

Pooled genome-wide CRISPR activation screening for rapamycin resistance genes in Drosophila cells

Abstract: Loss-of-function and gain-of-function genetic perturbations provide valuable insights into gene function. In Drosophila cells, while genome-wide loss-of-function screens have been extensively used to reveal mechanisms of a variety of biological processes, approaches for performing genome-wide gain-of-function screens are still lacking. Here, we describe a pooled CRISPR activation (CRISPRa) screening platform in Drosophila cells and apply this method to both focused and genome-wide screens to identify rapamycin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Specifically, CRISPRa might be considered a valuable tool for orthogonally validating immunity and fitness studies in I. scapularis. By overexpressing genes of interest in I. scapularis cells, one may complement RNAi-based technologies and develop small-or large-scale studies, such as commonly reported genomewide pooled CRISPRa screens in mammals and Drosophila (28,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, CRISPRa might be considered a valuable tool for orthogonally validating immunity and fitness studies in I. scapularis. By overexpressing genes of interest in I. scapularis cells, one may complement RNAi-based technologies and develop small-or large-scale studies, such as commonly reported genomewide pooled CRISPRa screens in mammals and Drosophila (28,30).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, CRISPRa might be considered a valuable tool for orthogonally validating immunity and fitness studies in I. scapularis. By overexpressing genes of interest in I. scapularis cells, one may complement RNAi-based technologies and develop small-or large-scale studies, such as commonly reported genomewide pooled CRISPRa screens in mammals and Drosophila (28,30). Collectively, the development of genetic tools for tick research offers unique avenues to identify crucial genes related to growth, physiology, immune signaling and detection of microbes.…”
Section: Discussionmentioning
confidence: 99%